Adverse events following immunization among children during primary immunizations in selected health facility of Himachal Pradesh - Sharma, Neeti; Pugazhendi, Sanchita; Semwal, Jayanti; Prakash, Kamli (Indian Journal of Community Health, 2023)
Background: Vaccine related problems are commonly reported after immunizations and are a matter of concern for health care professionals. A study on the pattern and rate of incidences of vaccine related problems was conducted among children undergoing primary immunizations. Materials and methods: The study was conducted in Zonal hospital, Solan, Himachal Pradesh. 150 mothers and their children undergoing immunization were enrolled in the study using systematic random sampling and followed on every immunization event until nine months. Vaccine related problems were enquired at every immunization events namely birth, six weeks, ten weeks, fourteen weeks and nine months using a self-structured tool to assess vaccine related problems among children. Results: Pain at vaccination site, redness and swelling, excessive crying, fever, and sleep related problems, feeding problems and fever were common AEFIs reported by mothers among children. Conclusion: AEFIs are frequent and need to be reported. None of the child had any severe reaction or hospitalization after immunization.